Analysis of Fire Safety Management in Construction Work at I Gusti Ngurah Rai Airport Bali - Hanif Safar; Fatma Lestari (Jurnal Impresi Indonesia, 2025)
Fire safety is an important aspect of construction project management, especially in strategic areas such as airports that are highly vulnerable to fire hazards. This study aims to evaluate the implementation of fire safety management on a construction project conducted by PT X at I Gusti Ngurah Rai International Airport, Bali, in 2024. The author used a case study method with a qualitative approach, which involved field observations, in-depth interviews with project personnel, analysis of safety documents, and analysis of relevant regulations. The results showed that PT X has implemented several key elements of fire safety management, including hazard identification, provision of light fire extinguishers (APAR), evacuation training, and emergency response procedures. However, some weaknesses were identified, such as the lack of regular inspections of fire protection equipment and limited socialization of safety procedures to all workers. This study recommends increasing supervision, providing ongoing training, and aligning practices with the latest regulations for improvement. The findings are expected to serve as a reference for similar construction projects in high-risk areas particularly in Indonesia.